HOTS QUESTION ON STUDENTS’ WRITING ABILITY IN REPORT TEXT AT BUSINESS MURNI SADAR POLYTECNIC - Doris Yolanda Saragih; Poltak Pardamean Simarmata (Politeknik Bisnis Indonesia, 2020)
This research was about applying HOTS question on students’ writing ability in report text at Business Murni Sadar Polytechnic , which the problem of this research was “What extent to the students’ writing ability in report text by applying HOTS question at Business Murni Sadar Polytechnic ?” and the objective of this research was to find out the extent of students’ writing ability in report text by applying high order thinking skill (HOTS) question at Business Murni Sadar Polytechnic. The method that used in this research was quantitative research design. The population of this research was students of Business Murni Sadar Polytechnic Population of this research were 100 students. The sample of this research were 60 students with divided into 30 students as experimental class and 30 students of as control class. The analysis of this research showed that the mean score of pre- test of the experimental group was 53, 566 and control group was 54, 1. The mean of post-test of the experimental group was 82, 066 and control group was 67, 033. Testing hypothesis showed that t-test (4,0003) was higher than t-table (1,671) at level of significant 5% for two tailed test. It meant that applying HOTS Question on students’ writing ability in report text gave a good contribution. Based on the result, it can be seen that the students’ writing ability in report text increased. It meant that there was an extent (improvement) of students’ writing ability in report text by applying HOTS Question at Business Murni Sadar Polytechnic.